Using journey mapping to understand the patient experience with selecting a Medicare part D plan using a pharmacy consultation service - Logan T. Murry; Arwa Al-Khatib; Matthew J. Witry (Elsevier, 2021)
Background: Patient experience with community pharmacy services can be informed by human-centered design principles and approaches. Pharmacy services may benefit from detailed evaluations of consumer experience and patient-centered service design. Objectives: To use an online journey mapping platform to understand the patient experience with selecting a Medicare Part D plan for individuals that did, and did not, use a free, pharmacy-led, Medicare Part D consultation service. Methods: This was a two-group cross-sectional survey study in a single, rural community pharmacy. Surveys consisted of 7 demographic items, 30 Likert-type items, and 7 open-ended response items. The pharmacy used purposeful convenience sampling to distribute a paper survey to individuals 65 years of age and older currently enrolled in Medicare Part D between June and August 2019. Surveys were distributed to 36 patients currently enrolled in a Medicare Part D plan, with 18 surveys distributed to patients who had previously used a pharmacy-led Medicare Part D consultation service and 18 surveys distributed to patients who did not use the service. Surveys were uploaded to an online journey mapping platform, producing data visualizations for each group. Multiple choice survey items were analyzed using descriptive statistics, wth service user and nonuser groups compared using Mann-Whitney U tests. Open-ended survey responses were coded by the research team using an inductive approach. Results: In total, 36 surveys were returned to the community pharmacy for a response rate of 100%. The journey map platform generated Persona, Empathy, and Current Journey outputs, which mapped Good Experiences and Bad Experiences within the Medicare Part D plan selection experience. Personas differed in their median household incomes ($25,000-$39,999 for service users compared to $50,000-$74,999 for nonusers). Empathy and Current Journey outputs showed that service users had a wider variety of emotions compared to non-users. Mann-Whitney U tests yielded 5 items with statistically significant differences (p-values <0.05) in the plan-selection experience, with both groups similarly uncertain about their plan decision. Qualitative responses indicate patient trust was universally important to a complex decision-making process. Conclusions: An online journey mapping platform provided insight into how patients experience a pharmacy service that extends beyond satisfaction. For community pharmacies providing Medicare Part D plan consultation services, pharmacies should consider how they can improve the service experience through communication style and patient-centered service design.